Why modern family planning needs of women is not met in South Gondar Zone, Ethiopia? - Gojjam Eshetie Ewunetie; Mamo Dereje Alemu; Muluken Genetu Chanie (Public Library of Science (PLoS), 2022)
Background Family planning is critical for the health of women and their families and it can accelerate a country's progress toward reducing poverty and achieving Sustainable Development Goals. Effective use of family planning methods helps couples achieve the desired number of children, contribute to improving maternal and child health which may help women avoid unwanted pregnancy, and reduce the risk factors for maternal and child deaths. Moreover, contraceptive prevalence and unmet need for family planning are key indicators for determining the level of improvements in access to reproductive health. So, this study aimed to identify the prevalence and associated factors of unmet need of modern family planning among reproductive-age women in the south Gondar zone. Methods A community-based cross-sectional study design was conducted in the southern Gondar zone among 528 reproductive-age women. Data were collected with pre-tested, structured, interviewer-administered questionnaires. Data were coded and entered into Epi info version 7 and exported to SPSS version 20. Bivariable and multivariable logistic regression models were applied. A P-value0.05 was considered to declare a result as significant at 95% CI. Result The overall unmet need in this study area was 22.6%, from whom 15.1% of respondents were wanted children later and 7.5% were wanted no more children. For women who had been visited by health care providers within 12 months before the study, women currently on menstrual status, the desired number of children, and induced abortion were found statistically significant. Conclusion The unmet need for FP was found high in the study area as compared to the national and regional prevalence. Women visited by health care providers, currently menstruating, the desired number of children, and history of induced abortion were significantly associated with the unmet need of modern FP. Health care providers and health extension workers need to visit regularly and promote appropriate and active IEC programs that address the provision of accurate information about the availability of the services and various contraceptive options including techniques to reduce and change perceived barriers to service utilization (such as rumors and misconceptions of FP).